The Analysis of Mood and Speech Function in the Tenth-grade English Textbook of Senior High School - Azkia, Zukhrufa Zahra Wina; Sarwanti, Sri; Rekha, Agnira (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2024)
This study is intended to analyze the narrative texts involved in the tenth-grade English textbook published by the Indonesian Ministry of Education and Culture In this case, this research only focuses on mood types and speech functions. This qualitative study uses discourse analysis. The writer analyzed the data using three stages outlined by Miles and Huberman (2014). The first process is data condensation, during which the writer selects, focuses, simplifies, abstracts, and transforms. In the second phase, the author presents the data using a coding system.The final step is to draw a conclusion or verify it. The writer in this step calculated the data into percentage and gives the description to describe the percentage. From the data and the analysis has done, there are 214 clauses found in the three narrative texts in the tenth-grade English textbook published by Indonesian Ministry of Education and Culture. Therefore, the dominant mood used in the narrative texts in the tenth-grade English textbook published by the Indonesian Ministry of Education and Culture is the declarative mood, with a total number of 191 clauses with a percentage of 89,25%. For the speech function, the percentage of the statement clauses was 89,25% (191 statements were found). The dominant speech function used in the narrative texts in the tenth-grade English textbook. This study has some consequences for how teachers choose words while teaching. The teacher might use a precise format when instructing the students so that they recognize what the teacher is saying. Furthermore, teachers must be able to select the appropriate words while expressing, asking, offering, and demanding while teaching English to students in the classroom so that the students can understand the teachers' statements, commands, questions, and offers.